VOCABULARY AS PART OF LINGUISTIC COMPETENCE IN SMA ENGLISH TEXTBOOKS IN INDONESIA - Sukur, Silvester Goridus (Universitas Swadaya Gunung Jati, 2020)
This research aims to reveal to what extent the textbooks developed for senior high school students all around Indonesia have provided or developed the materials for vocabulary learning purpose to promote students? competence in using English for their daily communication. This qualitative content analysis research was conducted with the content analysis research method and was carried out in Yogyakarta Special Territory from 2018 to 2019. The research data were collected and managed with the help of NVivo 11 Plus and NVivo 12 Plus Software. The data were gathered from three English textbooks for Senior High School Students: Bahasa Inggris X, Bahasa Ingris XI, and Bahasa Inggris XII, all of which were specifically developed by the Indonesian Government to be used by all SMA (Senior High School) students all over Indonesia. To achieve reliability agreement level of data, the Kappa Statistics reliability test was used; the result of which was > 0.75 (excellent). The research result shows that the contents of the three textbooks selected for this research in terms of vocabulary-related materials are not consistent; Not all textbooks and not all chapters presented the materials for the students to learn and improve their vocabulary. It is advisable that the English textbooks prepared all SMA students all over Indonesia develop materials or topics particularly the vocabulary consistently.